ROLE OF TEACHER IN FIGHTING HOAX IN INDONESIA - Toebagus Galang; Wahyu Widodo; Sapto Budoyo (Asosiasi Pengelola Publikasi Ilmiah (APPI) PT PGRI, 2022)
the article discusses on how Indonesian law tackles the dangers of hoaxes especially the role of teacher as educator in fighting it using a normative-juridical method of research. The result shows that there are obstacles that hinders the Indonesian Laws in Handling Hoaxes in the form of several factors that cause hoaxes to spread in Indonesia, such as the low interest in reading Indonesian people, and the low legal authority of Indonesia which is triggered by several factors such as the inability of the government to resolve cases of human rights violations which result in a low level of public trust in the government as can be seen from the many Hoax news that is spread, most of which often discredit or corner the government. To prevent this, it is necessary to make efforts to increase interest in reading for the community, and that effort can come from teacher as educator by campaigning for Turn-Back Hoax through not only their student but also to the community and for the government to increase the authority of the law by providing a positive image to the community.